2023
DOI: 10.1186/s12912-023-01361-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence and organizational commitment among nurses working in governmental hospitals in Jordan

Abstract: Introduction Nurses’ emotions and feelings in response to their environment and their ability to manage their emotions can significantly affect several aspects of their job. In Jordan, studies are still investigating whether emotional intelligence is significantly related to organizational commitment. Aim To investigate whether a significant relationship exists between emotional intelligence and organizational commitment among Jordanian nurses work… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Nurse managers possessed above-average EQ levels, which connects to previous research on the value of EQ to promote well-being and organizational committ-ment. 5 Attributes of HCL-HC in the Upholder dimension are emotional, social, and organizational awareness as well as mindful, others-oriented, and personal well-being, which are high EQ attributes. 8,9 AACN's data consistently show that units that implement HWE standards outperform those that don't use these standards.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nurse managers possessed above-average EQ levels, which connects to previous research on the value of EQ to promote well-being and organizational committ-ment. 5 Attributes of HCL-HC in the Upholder dimension are emotional, social, and organizational awareness as well as mindful, others-oriented, and personal well-being, which are high EQ attributes. 8,9 AACN's data consistently show that units that implement HWE standards outperform those that don't use these standards.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of emotional quotient (EQ) is described as being aware of one's own emotions and the emotions of others and how they correlate with each other. [5][6][7] Nurses with a high EQ can regulate their emotions and the emotions of others to achieve positive goals and outcomes. 5 Multiple studies have shown that a high EQ can help support emotional demands by reducing job stress and increasing satisfaction.…”
Section: Emotional Intelligencementioning
confidence: 99%
See 3 more Smart Citations